Rancang Bangun Prototipe Sensor Rasa Elektronik Berbasis Membran Selektif Ion - Danang Lelono; Kuwat Triyana; Sri Hartati; Finta Amalinda; Ummi Kaltsum; I Usuman (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2011)
Abstrack— Has successfully implemented aprototype sensor based electronic selectivemembrane. Chemical sensors based on ion selectivemembrane is to use a mixture of dicotyledonousphosphate (DOP) and Trioctyl methyl ammoniumchloride (TOMA), with a composition of 9 and 1.Taste sensor working electrode and referenceelectrode immersed in the sample test solution andconnected with ion meter. So that the signal can becaptured by the ion meter then use a buffer as theinterface becomes a high input impedance low outputimpedance. Measured signal is magnified by theamplifier so that it can be read by the display. Resultsshown by substraction of the signal referenceelectrode with the working electrode signal.The experimental results show DOP-based ionselective membranes and TOMA with a ratio 9 and 1have the ability to perform characterization andanionic response in a sample of five basic tastes ofsour, sweet, bitter, salty and umami and theconcentrations were varied from 0.1 mmol to 100mmol. While the response time is obtained at 4minutes to get stable data with measured values in thesample five basic tastes.Keywords— Ion selective membrane, DOP,TOMA, membran selektif ion, DOP, TOMA, five basictaste, ion meter,buffer, amplifier.